2018
DOI: 10.3171/2017.8.spine17370
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of corset adoption after single-level lumbar discectomy: a randomized controlled trial

Abstract: OBJECTIVEIn this paper, the authors sought to verify whether corset adoption could improve the short-term and midterm outcome scores of patients after single-level lumbar discectomy.METHODSA monocentric, randomized controlled trial of 54 consecutive patients who underwent single-level lumbar discectomy at the authors’ institution was performed from September 2014 to August 2015. Patients were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 16 publications
1
25
2
1
Order By: Relevance
“…Soliman et al [2] reported that the improvement in ODI at three months after surgery was significantly greater in the control group (p = 0.010), compared to the bracing treatment group. By contrast, a significant difference in ODI between the two groups was not reported at the follow-up in the studies by Yao et al and Zoia et al [3,4].…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Soliman et al [2] reported that the improvement in ODI at three months after surgery was significantly greater in the control group (p = 0.010), compared to the bracing treatment group. By contrast, a significant difference in ODI between the two groups was not reported at the follow-up in the studies by Yao et al and Zoia et al [3,4].…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 80%
“…Three studies [2][3][4] compared disability by assigning an Oswestry Disability Index (ODI) score to patients who received postoperative bracing and those who did not after surgery for lumbar degenerative disease. Of these, Soliman et al [2] and Yao et al [3] assessed the utility of bracing following posterior instrumented fusion and open TLIF, respectively, while Zoia et al [4] evaluated the efficacy of bracing treatment after single-level microdiscectomy.…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations